POLITICAL PARTIES. ELECTIONS: PROCESS OF ELECTIONS. ACTIONS STRATEGY - Teshaboyeva Nafisa Zubaydulla qizi; Abduvahobova Sevara Sobirjon qizi (Ta’lim innovatsiyasi va integratsiyasi, 2024)
Annotation: Uzbekistan has a multi-party system, but the ruling party, the Liberal Democratic Party of Uzbekistan (O'zLiDeP), dominates the political landscape. Other parties are allowed to operate, but they face significant restrictions and have little real power. Elections are held regularly in Uzbekistan, but they are often criticized for being unfair and undemocratic. There are a number of political parties in Uzbekistan, but O'zLiDeP is the largest and most powerful. O'zLiDeP is led by President Shavkat Mirziyoyev and controls a majority of seats in the Oliy Majlis, the country's parliament. Other political parties include the People's Democratic Party of Uzbekistan (PDPU), Milliy Tiklanish (National Revival), Adolat (Justice), and the Uzbekistan National Revival Democratic Party (UNDP).